Standardized Urine-Based Tuberculosis (TB) Screening With TB-Lipoarabinomannan and Xpert MTB/RIF Ultra in Ugandan Adults With Advanced Human Immunodeficiency Virus Disease and Suspected Meningitis - Cresswell, Fiona V.; Ellis, Jayne; Kagimu, Enock; Bangdiwala, Ananta S.; Okirwoth, Michael; Mugumya, Gerald; Rutakingirwa, Morris; Kasibante, John; Quinn, Carson M.; Ssebambulidde, Kenneth; Rhein, Joshua; Nuwagira, Edwin; et al. (In Open forum infectious diseases, 2020)
Background. Diagnosis of extrapulmonary tuberculosis (TB) remains challenging. We sought to determine the prevalence of disseminated TB by testing urine with TB-lipoarabinomannan (TB-LAM) lateral flow assay and Xpert MTB/RIF Ultra (Ultra) in hospitalized adults. Methods. We prospectively enrolled human immunodeficiency virus (HIV)-positive adults with suspected meningitis in Uganda during 2018–2020. Participants underwent standardized urine-based TB screening. Urine (60 mcL) was tested with TB-LAM (Alere), and remaining urine was centrifuged with the cell pellet resuspended in 2 mL of urine for Xpert Ultra testing. Results. We enrolled 348 HIV-positive inpatients with median CD4 of 37 cells/mcL (interquartile range, 13–102 cells/mcL). Overall, 26% (90 of 348; 95% confidence interval [CI], 21%–30%) had evidence of disseminated TB by either urine assay. Of 243 participants with both urine TB-LAM and Ultra results, 20% (48 of 243) were TB-LAM-positive, 12% (29 of 243) were Ultra-positive, and 6% (14 of 243) were positive by both assays. In definite and probable TB meningitis, 37% (14 of 38) were TB-LAM-positive and 41% (15 of 37) were Ultra-positive. In cryptococcal meningitis, 22% (40 of 183) were TB-LAM-positive and 4.4% (6 of 135) were Ultra-positive. Mortality trended higher in those with evidence of disseminated TB by either assay (odds ratio = 1.44; 95% CI, 0.83–2.49; P = .19) and was 6-fold higher in those with definite TB meningitis who were urine Ultra-positive (odds ratio = 5.67; 95% CI, 1.13–28.5; P = .04). Conclusions. In hospitalized Ugandans with advanced HIV disease and suspected meningitis, systematic screening with urine TB-LAM and Ultra found a high prevalence of urine TB test positivity (26%). In those with TB meningitis, urine tests were positive in over one third. There was little concordance between Ultra and TB-LAM, which warrants further investigation.
Keywords: HIV; Meningitis; TB-LAM; Tuberculosis; Xpert MTB/RIF Ultra.